Optimization Simulation Research of Lubrication Injection Parameters for Wide Tooth Cylindrical Gears - Xiangyu Li; Aihua Yang; Yumei Hu; Shuhua He (Jixie chuandong)
The numerical simulation of injection lubrication of high-speed wide gears and the improvement of lubrication effect are studied. Based on experimentally verified simulation methods，the oil injection lubrication simulation analysis of the oil-gas two-phase flow model of the high-speed wide-tooth cylindrical gear transmission is carried out. The result shows， the gas pressure field around the high-speed gear will seriously hinder the oil jet； excessive end face angle and unreasonable spray direction make it difficult for oil to lubricate the entire tooth surface of a wide gear. The simulation results of single-phase gas field are used to optimize the injection parameters. After that，the simulation results of two-phase flow verified the effectiveness of the optimization，which is，when the end face angle is 0，the nozzles on the meshing-in side are arranged symmetrically along the tooth width，and the nozzles on the meshing-out side are aligned with the meshing heating surfaces of the two gears. When spraying oil，it is more conducive to increase the oil and gas ratio and the convective heat transfer coefficient of the meshing tooth surface， thus，efficient lubrication and cooling of meshing tooth surface can be realized.